Clinicopathological features and programmed death-ligand 1 immunohistochemical expression in a multicenter cohort of uterine and ovarian melanomas: a retrospective study in Japan (KCOG-G1701s). Issue 3 (29th March 2022) - Yano, Mitsutake; Nasu, Kaei; Yasuda, Masanori; Katoh, Tomomi; Kagabu, Masahiro; Kobara, Hisanori; Matsuura, Motoki; Tokuyama, Osamu; Yamawaki, Takaharu; Wakahashi, Senn; Noguchi, Tomoko; Mizuno, Kaoruko; et al.
Abstract : The objective of this study was to propose prognostic factors and optimal treatment strategies by analyzing the clinicopathological features and programmed death-ligand 1 (PD-L1) expression. We analyzed 31 patients diagnosed with uterine or ovarian melanoma between 1997 and 2017 in the Kansai Clinical Oncology Group/Intergroup. Twenty-four and seven patients with cervical and ovarian melanomas were included, respectively. Immune checkpoint inhibitors were used in seven patients, and the objective response rate was 40%. Notably, two patients with objective responses had a high PD-L1 expression. Ten and four patients with cervical and ovarian melanomas, respectively, had high PD-L1 immunohistochemical expressions. Multivariate analysis revealed that tumor stage was an independent prognostic factor for progression-free survival in patients with cervical melanomas. In patients with ovarian melanomas, the 1-year cumulative progression-free and overall survival rates were 0 and 29%, respectively. Kaplan–Meier analyses revealed that age <60 years was associated with poorer progression-free and overall survivals in patients with ovarian melanomas. In patients with cervical melanomas, the 1-, 3-, and 5-year cumulative overall survival rates were 53, 32, and 16%, respectively. Histological atypia was associated with a poorer progression-free survival, but there was no difference in survival between patients who underwent radical hysterectomy and those who did not. The present study is a large cohort study of uterine and ovarian melanomas, which are aggressive tumors with a significantly poor prognosis, even after standard surgery and adjuvant therapy. The use of immune checkpoint inhibitors is a promising and effective treatment option.